Предмет: Математика,
автор: qwer975
(4x-5)(3x+7)-(x-2)(4x+2)=33x-9
Ответы
Автор ответа:
0
Ответ:
=-1
=2,75
Пошаговое объяснение:
(4x-5)(3x+7)-(x-2)(4x+2)=33x-9
12+28x-15x-35-(4+2x-8x-4)=33x-9
12+28x-15x-35-(4-6x-4)=33x-9
12+28x-15x-35-4+6x+4=33x-9
8+19x-31=33x-9
8+19x-31-33x+9=0
8-14x-22=0
4-7x-11=0
-7x=4x-11x
4-4x-11x-11=0
4x(x+1)-11(x+1)=0
(x+1)(4x-11)=0
x+1=0
=-1
4x-11=0
==2,75
Похожие вопросы
Предмет: Русский язык,
автор: monika2003
Предмет: Английский язык,
автор: Ksyusha2904
Предмет: Русский язык,
автор: ssdron1
Предмет: Математика,
автор: Татьяна11546